ANALYSIS OF WOMEN'S EMPOWERMENT BASED ON NON-FORMAL EDUCATION THROUGH SUSTAINABLE FOOD GARDEN PROGRAM - Hepy Tri Winarti (JIV-Jurnal Ilmiah Visi, 2022)
The purpose of this study was to analyze the process of implementing women's empowerment through the Sustainable Food Garden Program in the Sempaja Timur Village, Samarinda City. Methods This research uses a qualitative descriptive approach. The collection technique used interviews with program coordinators, RT heads, chairmen and members of the ACC Women's Group. Observation and study of documents in the form of reviewing photos of the process of implementing empowerment activities through Sustainable Food Garden Program. The data analysis technique uses data reduction, data presentation, and drawing conclusions. The validity of the data using triangulation of sources and techniques. The results of this study indicate that the process of empowering women through Sustainable Food Garden Program in the Sempaja Timur Village includes group capacity building in the form of non-formal education activities in the form of training and group coaching. implementation of women's activities by giving them the power to be independent, as well as monitoring and evaluation aimed at monitoring the progress and success of the program.